Analisis Yuridis Penyelesaian Sengketa Internal DPRD Kabupaten Bandung Melalui Pendekatan Alternative Dispute Resolution - Praniko Imam Sagita; Hendri Abdul Qohar (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Internal disputes within regional legislative institutions, specifically the Regional House of Representatives (DPRD) of Bandung Regency, constitute a phenomenon that potentially hinders institutional performance and public service. This research aims to juridically analyze the resolution of internal disputes within the Bandung Regency DPRD through an Alternative Dispute Resolution (ADR) approach. The research method employed is normative-empirical juridical, utilizing statutory and case study approaches. The results of the study indicate that internal disputes within the Bandung Regency DPRD encompass leadership conflicts, struggles for positions within council organs, and differences in political stances among factions. The ADR approach, through mechanisms of negotiation, mediation, and deliberation for consensus (musyawarah mufakat), has proven more effective than litigation in resolving internal institutional disputes within the DPRD. Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution provides the legal foundation for the application of ADR, while the principle of deliberation for consensus enshrined in Pancasila serves as the fundamental philosophy for dispute resolution. The primary obstacles to the implementation of ADR include factional sectoral egos, the absence of specific regulations governing the resolution of internal DPRD disputes, and a weak culture of political compromise. This research recommends the necessity of formulating ADR-based guidelines for resolving internal DPRD disputes, which should be integrated into the council's rules of procedure.